Let a = 12, b = -20,

(A) A^-b^ my variables in this expression are a and b. exponent of 3 on each of them. 12^3– (-20)^3 variable a is 12 and variable b is -20.

(B) (a – b)(a^2 + ab +b^2) This expression also uses variables a and b.

A = -256

B - (a-b)(a^2 + ab +b^2) = (12 - (-20)) (12^2 + 12*-20 + (-20)^2)

= (32) (144 -240 +400) =(32)(304)

=9728

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up